DEVELOPMENT OF WOODCERAMICS FROM TROPICAL FLORA - Itsaree Howpinjai; Nikhom Laemsak; Pongsak Hengniran (BIOTROPIA, 2020)
Woodceramics are porous carbon or hybrid materials derived from woody materials impregnated with thermosetting resin and vacuum-carbonized at high temperatures. Woodceramics have become commercially valuable due to their applications in heaters, gas filters, absorbents, and humidity and temperature sensors. Hence, this study aimed to determine the suitable conditions for producing woodceramics from various materials and to evaluate their potential applications. The specific surface area (SSA), pore volume, pore diameter, and adsorption isotherm of woodceramics made from bamboo, pine, eucalyptus, rubberwood, and oil palm shell particleboards were obtained using the Brunauer–Emmett–Teller (BET) method. The average pore diameter was classified as mesoporous (2–50 nm). The SSA and adsorption isotherm results of the woodceramics made from eucalyptus indicated that this species can be used as activated charcoal, and its volume electrical resistivity was similar to that of a semiconductor. When carbonized at maximum temperatures of 800 °C and 1,000 °C, the electromagnetic shielding effectiveness (ESE) of the woodceramics ranged from approximately 20–60 dB within a frequency range of 800–2,200 MHz. This ESE value was higher than those of materials woven from boron carbon fiber, carbon boron, and stainless steel fiber-filled thermoplastics. Moreover, the production cost of woodceramics was lower compared to commercial alternatives.